Measurement of the tibial plateau angle of normal small-breed dogs and the application of the tibial plateau angle in cranial cruciate ligament rupture - Seo, Beom Seok; Jeong, In Seong; Piao, Zhenglin; Kim, Minju; Kim, Sehoon; Rahman, Md Mahbubur; Kim, Nam Soo (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: In Korea, small dogs are more common than large breeds. This study was performed to measure the influence of body weight, sex, breed, age, and cranial cruciate ligament rupture (RCCL) on the tibial plateau angle (TPA) in small-breed dogs. Materials and methods: A total of 274 dogs (221 normal dogs and 53 RCCL dogs) were selected for this study based on medical records. The TPA was measured from stifle joint radiographs. The dogs were divided according to body weight, sex (male and female; normal and neutered), age, breed, and RCCL, and the TPAs of the dogs were compared. Results: In general, the TPAs of male dogs were significantly (p < 0.05) higher than those of female dogs, and those of healthy neutered dogs were higher than those of healthy intact dogs. The TPA had a tendency to increase along with the animal’s age but was not significantly different among the four age groups. In general, the TPA of RCCL dogs was 27.12° ± 0.62°, which was significantly higher (p < 0.001) than that of normal dogs (20.21° ± 0.32°), indicating that an increased TPA is associated with a higher risk for RCCL. Similar results were also observed among dogs with similar body weights, breeds, and ages for male and female RCCL dogs. Conclusion: This study suggested that the sex and neutering status of dogs could affect the TPA. This study also confirmed the use of TPA in the veterinary clinic as a possible indicator of RCCL, as the TPA is higher in RCCL dogs than in normal dogs. Adv. Vet. Anim. Res., 7(2): 220-228, June 2020